Valuation Analysis of Combined Company Value Through Acquisition Process: Case Study of PT Vale Indonesia Tbk and PT Kapuas Prima Coal Tbk - Kurniawati, Yuni; Syawaldi Afwan, Ahmad; Pradina, Dinda Ayu; Heikal, Jerry (Jurnal Sains dan Teknologi, 2024)
This study aims to analyze the valuation of the combined company through M&A valuation and structuring models. The financial calculations considered in this analysis are based on data from the statements of financial position, income statements, and cash flow statements over the past three years for PT Vale Indonesia Tbk and PT Kapuas Prima Coal Tbk as case studies in this article. Data collection for this research was obtained from the IDX website, which provides historical stock data. This research was conducted to identify the feasibility of the acquisition of PT Kapuas Prima Coal Tbk by PT Vale Indonesia Tbk using an inter-company financial projection approach. The valuation and M&A structuring methods used include Discounted Cash Flow (DCF) analysis, market comparison, and valuation based on previous transactions. Information on specific techniques, assumptions made, and the analysis process will enhance the reader's understanding of the validity of the results. The analysis results, comparing the Equity Values of the target company, the acquiring company, and the new company, indicate that the Equity Value of Newco is significantly higher than the sum of the individual Equity Values of the target companies. The benefits of the research include providing important information that can be used by company management, investors, and other stakeholders in making decisions related to acquisitions and company mergers.